Clinical and microbial impact of screening kidney allograft preservative solution for bacterial contamination with high‐sensitivity methods. (5th June 2013) - Bertrand, Dominique; Pallet, Nicolas; Sartorius, Albane; Zahar, Jean Ralph; Soussan, Rebecca Sberro; Lortholary, Olivier; Legendre, Christophe; Mamzer, Marie‐France
Summary The clinical and bacteriological consequences of routinely performing highly sensitive bacterial screening of kidney transplant preservation solution (PS) are not known. To evaluate the clinical and microbiological impacts of this strategy, we retrospectively analyzed 200 consecutive kidney allograft recipients from March 2009 to February 2011 for whom PS samples were routinely screened. PS were inoculated into aerobic and anaerobic blood culture bottles, as well as blood agar plates. A rectal swab for extended‐spectrum β‐lactamase‐producing Enterobacteriaceae (EBSL‐PE) faecal carriage was also routinely obtained from each patient at admission and every 7 days until hospital discharge. In addition, a standard culture of drain fluid was collected on the day after kidney transplantation. Complete samples and cultures of PS were performed in 165 cases (82.5%), and 62 (37.6%) had positive blood culture results. The most frequent microbial agent isolated was coagulase‐negative staphylococci (51.8%). Of these 62 positive samples, only seven (11.3%) were confirmed to contain the same organism by the standard culture method. Drain fluid and PS culture positivity with the same microorganism occurred in only two patients. Of the 62 patients with positive PS cultures, 26 (41.9%) received pre‐emptive antibiotic therapy initiated within 48 h post‐transplant. During the hospitalization period, patients with a positive PS culture, regardless of whether they received pre‐emptive antibiotic therapy, did not exhibit any invasive infections (urinary, blood, peritoneal or wound) related to the microorganisms isolated in the PS. Patients with positive PS cultures who were treated with antibiotic therapy acquired significantly more colonizing ESBL‐PE than patients who did not receive antibiotics (53.8% vs. 16.6%; P = 0.01); these patients also developed more clinical infections related to the ESBL‐PE (23.1% vs. 5.2%; P < 0.01). The use of antibiotics for patients with positive PS cultures was an independent risk factor for ESBL‐PE acquisition in both univariate and multivariate analyses. In conclusion, the use of more sensitive culture methods increases the rate of bacterial contamination of PS and is associated with an increased prescription of antibiotics and increased ESBL‐PE carriage and related infections. Therefore, the systematic use of PS blood bottle cultures in kidney transplantation may have no benefit and might increase the rate of ESBL‐PE emergence.